Appointment system in an environment of limited resources: the case of outpatient department clinics in Thailand - Boonma, Pochara (2012)
Previous research has mostly been aimed at improving service facilities and reducing unnecessary activities and staff; this has been achieved by implementing the Lean concept or reengineer processes, in order to improve the efficiency and effectiveness. This leads to a research gap, since no researcher investigates factors affecting satisfaction of doctors and patients when a medical appointment system is used. This research focuses on appointment systems in healthcare services in Thailand, providing an in-depth investigation of factors or variables affecting patient and doctor satisfaction. Although the medical resources in Thailand are limited, a study of Thailand‟s medical services has been selected as it can offer relatively lower expenses and provides equivalent or better service levels than developed countries. Literature reviews based on medical appointment systems show clearly that the general purpose of using these systems is to balance patients‟ waiting time, doctors‟ idle time and doctors‟ overtime. With respect to designing a medical appointment system and modelling its environments, patient pathways have to be considered. Using interviews from seven medical staff, in addition with observations at two hospitals, this study analyses patient scheduling within three different types of healthcare provider: small clinics or hospitals, public or small-to-medium-sized hospitals and large private hospitals or specialty clinics. The generalized patient pathway is newly developed and the activities of the patient pathway consist of registrations and medical records, examinations, vital signs, meeting doctors, making payments, prescriptions and referrals. 224 patients and 96 doctors participated in this study. The results indicated that there were several factors affecting the patient‟s satisfaction levels. These included bottleneck processes, their perspective on waiting times and doctors‟ treatment times for new and old patients. This research also included the opinions of various types of doctors on activities at outpatient department clinics. However, some of the perspectives of patients and most of the perspectives of doctors cannot conclude that two variables are dependent. The limitations of this research are the time constraint and the number of respondents.